Aberrant Expression of Cardiac Troponin-T in Lung Cancer Tissues in Association With Pathological Severity - Tsuruda, Toshihiro; Sato, Yuichiro; Tomita, Masaki; Tanaka, Hiroyuki; Hatakeyama, Kinta; Otsu, Misa; Kawano, Aya; Nagatomo, Keiko; Yoshikawa, Naoki; Ikeda, Ryuji; Asada, Yujiro; Kaikita, Koichi (Frontiers in Cardiovascular Medicine, 2022)
Background Cardiac troponin-T (TNNT2) is exclusively present in cardiac muscle. Measurement of TNNT2 is used for diagnosing acute coronary syndrome. However, its expression may not be limited in myocardium. This study aimed at evaluating the expression of TNNT2 in neoplastic tissues. Methods and Results We used paraffin-embedded blocks of 68 patients with lung cancer (age, 68 ± 11 years old; early-stage, 33; advance-stage, 35) at Miyazaki University Hospital, Japan between January 1, 2017, and March 31, 2019. We stained the slide sections with primary monoclonal antibody against TNNT2 protein, and assessed the frequency of positive staining, and its association with pathological severity. In addition, we examined whether TNNT2 gene is detected in lung cancer tissues of four patients using reverse transcription-polymerase chain reaction. Immunoreactivity for TNNT2 protein was present in the cytoplasm and nucleus of lung cancer cells. The frequency was 37% (25 of 68) in all patients and was irrespective of histologic type (six of 13, squamous cell carcinoma; 18 of 50, adenocarcinoma; 0 of 4, neuroendocrine cell carcinoma; 1 of 1, large cell carcinoma). The prevalence increased with pathological staging [9% (3 of 33) at early-stage (Stage 0–I); 63% (22 of 35) at advance-stage (Stage II–IV and recurrence)]. In addition, frequency of positive staining for TNNT2 increased with pleural (χ2 = 5.877, P = 0.015) and vascular (χ2 = 2.449, P = 0.118) invasions but decreased with lymphatic invasion (χ2 = 3.288, P = 0.070) in specimens performed surgical resection. Furthermore, TNNT2 mRNA was detected in the resected squamous cell carcinoma and adenocarcinoma tissues. Conclusions Our data suggest the aberrant expression of TNNT2 in lung cancer and its prevalence increases with pathological severity.